Pengaruh Penambahan Serbuk Galam Sebagai Pengganti Agregat Halus Pada Campuran Beton Mutu Normal - Anggarini, Elia Anggarini; Dyah Pradhitya Hardiani; M. Rizky Maulana Teguh (Universitas Muhammadiyah Surabaya, 2024)
The utilization of waste from wood cuttings is uncommon, and one of the wastes that is rarely employed is the leftovers of galam wood or galam powder cuttings. On this basis, a study entitled